2017
DOI: 10.1007/s40257-017-0318-5
|View full text |Cite
|
Sign up to set email alerts
|

Topical Corticosteroid Concerns Among Parents of Children with Psoriasis versus Atopic Dermatitis: A French Multicenter Cross-Sectional Study

Abstract: Using the TOPICOP questionnaire and a VAS, we found the level of TCC for the parents of pediatric patients with psoriasis to be similar to that for parents of pediatric patients with AD. As TCC is an issue in patients with psoriasis, future research is warranted to assess whether therapeutic education lessens TCC and improves treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Studies (12,13) have found that parents of girls had a higher TOPICOP score, while another study (5) found that mothers had higher TOPICOP scores. A study of adults and children with various skin conditions also found that female participants had greater steroid phobia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (12,13) have found that parents of girls had a higher TOPICOP score, while another study (5) found that mothers had higher TOPICOP scores. A study of adults and children with various skin conditions also found that female participants had greater steroid phobia.…”
Section: Discussionmentioning
confidence: 99%
“…It was also recently used to assess steroid phobia associated with psoriasis. (5) Steroid phobia may be partly attributed to the excessive or exaggerated risks depicted by the Internet, family/friends and even medical professionals. A study by Smith et al (6) reported that a third of survey participants received misinformation in the form of exaggerated risks from friends/family and over the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid phobia is prevalent in dermatology patients and may result in delayed treatment initiation and poor disease control. 7,8,20‐25 . Corticosteroid phobia even exists among healthcare providers, where the highest scores have been found in healthcare nurses, GPs, and pharmacists and the lowest in dermatologists 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis severity at the time of the survey was assessed using the Patient-Oriented Eczema Measure (POEM) 14 ; a sevenitem, validated, self-reported outcome tool about the frequency of signs and symptoms (itch, sleep disturbance, dryness, flaking, weeping or oozing, bleeding, and cracking) in the past 7 days. The final score ranges from 0 to 28 and was divided into five rank order categories: clear or almost clear (0-2), mild (3-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16), severe (17)(18)(19)(20)(21)(22)(23)(24), and very severe eczema (25-28). 15…”
Section: Patient-oriented Eczema Measurementioning
confidence: 99%
“…13,14 Recently, this scale has also been used to assess steroid phobia associated with psoriasis. 15 Steroid phobia can be partially attributed to the significant (or overstated) risks presented by the Internet, friends or family, and even medical professionals. The questionnaire-based study by Smith et al reported that 33% of participants had received false information in the form of overstated risks conveyed by friends, family, and the Internet.…”
mentioning
confidence: 99%